Análisis y Diseño de Propuestas de Reforzamiento de la Superestructura del Puente sobre el Río La Cruz - Ulate Ovares, David (Instituto Tecnológico de Costa Rica, 2011)
Many bridges in Costa Rica have the need to be strengthened due to the poor state in which they are or in some cases with the objective of updating with the governing specifications for the design of this type of structure. This project was raised as to the objective of finding a bridge that belonged to the national road network that had the need to enhance its strength capacity and hence propose a strengthening system based on fiber reinforced polymer materials which comply with this objective. To achieve this objective, the La Cruz river bridge superstructure was analyzed. In this analysis several structural models were carried out as the current element strength was calculated, to finally determine the amount of material of the reinforcing system that was needed to comply with the demanded load conditions. A carbon fiber strengthening (CFRP) system was proposed. After the result analysis it was possible to determine that the CFRP system was the one that offered the most number of advantages when compared to a traditional strengthening system like a steel sheet system.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2011.
Keywords: Concreto; Fibras; Carbono; Sostén; Polímeros